Academician prof. dr. Goran Filipi (1954-2021) - Furlan, Metka (Slavia Centralis, 2021)
The composition is dedicated to the memory of academician prof. dr. Goran Filipi, a long-time associate of the Department of Applied Linguistics and the Department of Italian Studies at the Faculty of Humanities of the University of Primorska.
Keywords: in memoriam; Goran Filipi; academician; Slovenian linguistics; Croatian linguistics